Game Cerita Alkitab untuk Sekolah Minggu - Harry Sakti; Liliana Liliana; Kristo Radion Purba (Jurnal Infra, 2017)
Sunday school is a place for children to learn and teachers to teach in the church. Church through Sunday school convey God's Word to toddler, kindergarten and grade 1 to grade 6 elementary school. Today, secular education has uses multimedia, but there are some Sunday school that has not been able to use multimedia and having difficulty finding multimedia that can be easily operated.Therefore, a multimedia application that can be easily operated by a computer was created. Game Cerita Alkitab untuk Sekolah Minggu is an application that is useful to convey the Bible story and invites users to play with illustrations in the form of images, sounds, text, and video.Application contains the story of creation, Noah and the Flood, the Tower of Babel, and Jonah from the Bible, as well as the 9 mini games. The result is an application that can be used by the sunday school, both the sunday school teacher to deliver the Word of God and the sunday school children to play.